Spectrophotometic Determination of Trace Zinc in Milk Powder by Ethyl Rhodamine B - Dong, Wenli; Xu, Gang (Asian Journal of Chemistry, 2014)
In the presence of the surfactant gum Arabic, the Zn(II)-SCN–-ERB (ERB = ethyl rhodamine-B) ternary chromogenic reaction system was studied. The results showed that, in the acetic acid-sodium acetate medium of pH 5.0, Zn(II)-SCN–-ERB forms a rose red complex of 1:4:2 at room temperature. The complex has a maximum absorption wavelength of 625 nm, a zinc content of 0.16-8.00 μg/25 mL conforming to the Lambert-Beer’s law, a molar absorption coefficient e625 of 1.02 × 105 L mol-1 cm-1 and a detection limit of 0.045 μg/25 mL. Using this method to determine the trace zinc in milk powder, the relative standard deviation is less than 2 % and the results are satisfactory.